Evaluation of the Development Strategies Village Breeding Center Peranakan Ongole (PO) Cattle Based on Swot Analysis - Muhammad irvan Ali; Muhammad Halim Natsir; Kuswati (Jurnal Ilmu-Ilmu Peternakan, 2023)
The research revealed that the appropriate strategy for the development of local cattle is influenced by both internal and external factors, such as the age of farmers, the educational level of farmers, the experience of cattle, the main job of farmers, availability ofland, knowledge of cattle farm management, use of technology and access to funding, and government support. This research aims to evaluate the development of the PO village breeding center based on internal and external factors. The research methodology employed involved conducting surveys, interviews, and documentation of cattle farmers, livestock group leaders, and Bojonegoro livestock department officials as sources of information. The method used in this study was purposive sampling. Descriptive quantitative and SWOT analyses were carefully applied to the available data. The internal factor analysis yielded a total value of 1.03 on the positive X-axis, while the external factor had a value of 0.15 on the positive Y-axis. As a result, the SWOT analysis shows the development of a PO village breeding center in quadrant I, which indicated that the program for developing a village breeding center was on the right track (aggressive) by continuously implementing growth strategies. Developing the source area forPO cattle has excellent potential to enhance the productivity and quality of PO cattle produced. The development strategy of PO cattle village breeding center should focus on the potential strength aspect of the capacity of local regions and farmers' support.